PENGARUH MEDIA VIDEO ANIMASI GIZI SEIMBANG TERHADAP PENGETAHUAN DAN SIKAP GIZI SEIMBANG SISWA KELAS IV SD HANG TUAH 10 JUANDA - Putri, Dila Lintang Harmanto (STIKes Mitra Keluarga, 2023)
Introduction : Wrong eating habit in elementary school students make nutritional problems. Balanced nutrition education needed by learning media can attract elementary school students’s attention. This investigation seeks to determine the effect of delivering information on balanced nutrition through the use of animated videos on the knowledge and attitudes of fourth-grade students at SD Hang Tuah 10 Juanda, Sidoarjo Regency. Method : Quantitative Research with QuasyExperimental trough Pre Test Post Test Control Group. The sample wasfourth grade pupils at SDHang Tuah 10 Juanda with 96 students. Results:The paired sample T-test revealed that the mean scores for knowledgeand attitude differ before and after the animation video interventionwith sig value (0,00) < 0,05. Independent T-Test shows sig value (0,00) <0,05. Conclusion : Animation in video content influences the knowledgeand attitudes of fourth-grade pupils at SD Hang Tuah 10 Juanda.